Liquid phase low temperature sintering of niobate and cerate fine powders - Shlyakhtin, O. A.; Orlov, A. V.; Oh, Young-Jei (SPRINGER, 2006)
The efficiency of simultaneous application of chemically-derived starting powders and melt-forming sintering aids in low temperature sintering has been demonstrated. Doping of cryochemically processed BiNbO4 powders with CuO/V2O5 causes reducing sintering temperatures from 850-900 degrees C to 700-720 degrees C. Similar doping of Zn3Nb2O8 fine powders allows to obtain ceramics with density 97-98% and Q x F values up to 40 000 GHz at T > 720 degrees C. The sintering of solution-derived BaCeO3 powders doped with CuO results in dense ceramics at T = 1000 degrees C. Morphological evolution during sintering was observed using hot stage SEM. Low temperature liquid phase sintering of fine powders is rather sensitive to the traces of secondary phases and to the micromorphology of starting powders though observed reduction of sintering temperatures is substantially larger than for traditional liquid phase sintering of coarse-grained oxide powders.
Keywords: MICROWAVE DIELECTRIC-PROPERTIES; DOPED BARIUM CERATE; BINBO4 CERAMICS; BACEO3; BETA-BINBO4; ZR; BI; ND